Effects of Measurement Errors on Systematic Risk and Performance Measure of a Portfolio - Lee, Cheng F.; Jen, Frank C. (Journal of Financial and Quantitative Analysis, 1978)
Cheng F. Lee, Frank C. Jen, Effects of Measurement Errors on Systematic Risk and Performance Measure of a Portfolio, The Journal of Financial and Quantitative Analysis, Vol. 13, No. 2 (Jun., 1978), pp. 299-312